Improving Vocabulary Reading Skills with Word Card and Picture Card for Moderate Intellectual Disabilities - Yohanes Subasno; Klemensia Nini; Consita Densi (Department of Special Education, 2022)
Teaching reading functional vocabulary to students with intellectual disability (ID’s) is a challenge for teachers in special schools. They face many obstacles in teaching vocabulary which are caused by various factors, especially student characteristics and learning structures that are less practical and tend to be academic. This study aims to measure the effectiveness of using word cards and picture cards to improve vocabulary reading skills in moderate ID’s students. The type of research applied is single subject research, with multiple baseline across subject designs. The research subjects were two moderately ID’s students in grade 5 and grade 2 SLB-C1 Bhakti Luhur Malang. An instructor and an observer played an important role in this study. The experimental instrument used is Lesson Plan which consists of three units, each teaching two vocabularies. Data analysis is carried out by performing graphical inspections that focus on trend, latency, and level changes. The effectiveness was confirmed by Percentage of All Non-overlapping Data (PAND) in the intervention condition against the baseline-1 condition. The results showed that with the intervention, the target behavior in the form of vocabulary understanding had a trend of grades rising gradually touching a high level of score, and settling at a high level in the baseline-2 condition. The average PAND for subject-1 reached 80.55 percent (effective), and subject-2 reached 96.67 percent (very effective).